The origin, development and diversity of Islamic feminism - Muhamad Shukri, Abdul Salam; Owoyemi, Musa Yusuf (Universiti Kebangsaan Malaysia, 2016)
The article surveys the feminist movement in Islam by delving into its origin, development and diversities within the Islamic tradition. The article starts its survey from the very beginning of the Islamic religion to the time after the demise of the Prophet and the modern and contemporary periods. Using the historical and analytical methods, the paper looks at the spectrums of the Muslim women struggle for their rights and the different dimensions that this religion itself. The submission of this paper is that, just as in other feminist movements from other traditions, the Islamic feminist movement is diverse and varied in its approach to the issue of claiming the rights of Muslim women. There are those advocate for the reinterpretation and restructuring of the religion to meet modern day demands and views of women and because of their feeling of a strong sense of rejection and they hold that the Islamic religion should abdicate talking it views about women and embrace modern reforms concerning the rights of women in the society. On the other hand, there are others who want the religion to remain as it is while the rights of women are respected and given due regards as was the case during the time of the Prophet. Thus, all these points to diversity of the discourse in the Islamic Tradition and speak of the fact that women's right is a very important issue in the contemporary Muslim societies which needs serious attention from Muslim scholars and leaders alike.